The Influence of Participation, Motivation and Family Environment on Increasing the Spirit of Entrepreneurship - Firman Syah; Aulia Aulia; M. Hidayat (Borong Newinera Publisher, 2023)
This research is a descriptive research with a quantitative approach. The purpose of this study was to determine the effect of partisipation, motivation and family environment partially on increasing the entrepreneurial spirit of students at the Faculty of Economics and Business, University of Muhammadiyah Makassar. Data were analyzed use multiple linear regression and analysis using the SPSS version 23. Population are students of the Faculty of Economics and Business, University of Muhammadiyah Makassar. The samples obtained amounted to 213 using probability sampling techniques. Test the validity of the data using validity and reliability tests. Data were analyzed using the classical assumption test, t test and the coefficient of determination. The research results obtained: 1. Participation has a positive but not significant effect on increasing student entrepreneurial spirit; 2. Motivation has a positive and significant effect on increasing student entrepreneurial spirit; and 3. The family environment has a positive and significant effect on increasing the entrepreneurial spirit of students.